Systematic review for orthodontic and orthopedic treatments for anterior open bite in the mixed dentition - Lucia Pisani; Laura Bonaccorso; Rosamaria Fastuca; Raffaele Spena; Luca Lombardo; Alberto Caprioglio (SpringerOpen, 2016)
Abstract Background The treatment options for the early treatment of anterior open bite are still controversial. The aim of this study was to evaluate the actual available evidence on treatments of anterior open bite in the mixed dentition in order to assess the effectiveness of the early treatment in reducing open bite, the most efficacious treatment strategy and the stability of the results. Materials and methods A literature survey was done on November 15, 2015, by means of appropriate Medical Subject Headings (MeSH) using the following databases: PubMed, EMBASE, Cochrane Library, LILACS, VHL, and WEB OF SCIENCE. Randomized clinical trials and studies with a control group (treated or untreated) were then selected by two authors. Trials including patients with syndromes or in the permanent dentition and studies concerning treatment with extractions, full-fixed appliances, or surgery were not considered. Full articles were retrieved for abstracts or titles that met the initial inclusion criteria or lacked sufficient detail for immediate exclusion. Results Two thousand five hundred sixty-nine studies about open bite were available; the search strategy selected 240 of them. Twenty-four articles have been judged suitably for the final review, and their relevant data were analyzed. Discussion Although this review confirms the effectiveness of early treatment of open bite, particularly when no-compliance strategies are employed, meta-analysis was unfeasible due to lack of standardization, important methodological limitations, and shortcomings of the studies. Conclusions A more robust approach to trial design in terms of methodology and error analysis is needed. Besides, more studies with longer periods of follow-up are required.